THE INFLUENCE OF PRINCIPALS’, TEACHERS’ AND STUDENTS’ ATTITUDE ON READINESS TO ADOPT e-LEARNING IN SECONDARY SCHOOLS IN KITUI DISTRICT, KENYA - Mulwa, Angeline Sabina; Kyalo, Dorothy Ndunge (European Scientific Journal, ESJ, 2013)
﻿Studies conducted in the field of ICT use in secondary schools reveal that, although in the past few years teachers and students have enjoyed adequate access to an assortment of ICTs such as computers, laptops, projectors printers, e-blackboards, mobile phones for use n integration of teaching and learning in schools, the level of utilization of the ICTs by teachers and students in Kitui District is still minimal. This study sought to examine the relationship between Principals, teachers’ and students’ attitude on utilization of ICTs and the readiness to adopt e-learning in curriculum implementation at secondary school level. The major objective of the study was to establish the extent to which the attitude of principals, teachers and students influence readiness to adopt e-learning in secondary schools in Kitui District. Cross–sectional survey research design was adopted for the study. A sample of 66 principals, 66 teachers and 347 students, were involved in the study. The multiphase sampling procedure was adopted for this study. Data were collected using questionnaires and an observation schedule. The resultant information was analyzed by employing the quantitative approach which involved descriptive and inferential statistical procedures. The findings of the study reveal that the attitude held by secondary school Principals and Teachers had no significant influence on the schools’ readiness to adopt e-learning. However, the attitude held by students had a significant influence on the schools’ readiness to adopt e-learning. The study recommends that the government should plan to address the issue of e-learning infrastructure by availing e-learning equipment, enhancing connection to reliable sources of power, improving connectivity to various internet services and augmenting Human Resource ﻿capacity by organizing training programmes for Principals, Teachers and Students. Secondary schools should employ support staff members such as computer laboratory technicians or assistants before embarking on full-scale implementation of e-learning in schools in Kitui District and, indeed, all other remote semi-arid districts in Kenya. This will enhance positive attitude and confidence that e-learning can be successfully adopted in secondary schools in Kenya regardless of the location of the school.